Comissões permanentes e política de recrutamento nas Assembléias Legislativas de Minas Gerais, Rio de Janeiro e Rio Grande do Sul - Thiago Rodrigues Silame (2009)
This paper aims to contribute to the growth of literature on subnational legislation, with the theme parliamentary recruitment for the system of standing committees in the legislative assemblies of Minas Gerais, Rio de Janeiro, and Rio Grande do Sul. It is argued in this paper that the recruitment standard for strategic committees varies depending on the extent of institutional development of the system of committees and the capacity of the oppositions performances. Due to the current federalism in Brazil, it is notable the existence of subsystems of parties, which allowed us to verify different degrees of party structuring of political competition in the surveyed states and allowed us to assume that the oppositions have greater possibility of action on structured subsystems of parties. Furthermore, it was found through objective criteria, the degree of the standing committees structuring in the assemblies analyzed. The results of this study point in the sense that the political and institutional variables matter in the recruitment of parliamentary committees for strategic. In political contexts where the opposition is represented and is active, party loyalty is an important criterion considered by the leader to indicate the parliamentary for the committees. Where the system of committee was more developed, expertise and seniority seemed to be important attributes that the parliamentarian should have to integrate strategic committees. In scenarios of low competitiveness of oppositions and low development of the system of committees, it is observed wide margin of parliamentarians action signaling a distributive dynamic of legislative work.